What makes a Die-Hard Entrepreneur? Trying, or Persisting in, Self-Employment - Andrew E. Burke; Felix R. FitzRoy; Michael A. Nolan (Max Planck Institute of Economics, 2005)
The paper makes three contributions to the economics literature on entrepreneurship. We offer a new measure of entrepreneurship which accounts for variations in persistence in self-employment. We outline an econometric methodology to account for this approach and find that it is superior to probit/logit models which have dominated the literature. While our results indicate that this existing literature is good at explaining an individual's propensity to try self-employment, we find that entrepreneurial persistence is determined by a different model and unearth some new insights into the roles of early career experience, finance, role models, gender and the unemployment push effect.
Keywords: C25; J23; 330; Self-employment; entrepreneurial persistence; count data; Unternehmer; Selbstständige; Unternehmensentwicklung; Zähldatenmodell; Erwerbsverlauf; Schätzung; Großbritannien